Epidemiological Assessment of Cassava Mosaic Disease in a Savanna Region of the Democratic Republic of Congo - Biola, Clara Funny; Mukendi, Remy Tshibingu; Kalonji-Mbuyi, Adrien; Nkongolo, Kabwe K (International Journal of Sustainable Agricultural Research, 2022)
An epidemiological survey was conducted, from September 2009 to January 2010 in 206 famers’ fields located across 21 cassava-growing localities of Ngandajika territory in Lomami province (central part of Democratic Republic of Congo (DRC), to determine distribution and status of Cassava Mosaic Disease (CMD). Parameters related to the identification and the evaluation of CMD (incidence, severity and gravity) and number of adult whitefly vector were assessed. CMD was present in all localities surveyed and varied according to the localities and varieties. CMD incidence was low at the INERA station (4.33%) but high in Kafumbu (74.55%). Disease severity was low at the INERA station (1.09) but high in Kafumbu (2.67). Gravity was low at the INERA station (2.99%) and elevated in Quartier Congo (67.82%). The mean of adult whitefly populations varied with sites. However, the whiteflies were more abundant in Mpunga (3.65) compared to the INERA station (1.09). Overall, 71 % of varieties showed varying degrees of sensitivity to CMD. The results of this study revealed that the health status of cassava in Ngandajika is alarming and deserves sustained intervention. Adequate and effective control methods must to be in place to reduce the inoculum levels and the speed of CMD propagation and to limit yield losses caused by this disease.